Facile fabrication of flexible, bendable and knittable electrode with PANI in the well-defined porous rEGO/GP fiber for solid state supercapacitors. (September 2020) - Niu, Jingye; Li, Jinmei; Liu, Peng
Highlights: Flexible, bendable and knittable PANI@rEGO/GP fiber electrode was designed. By electropolymerizing the adsorbed aniline in honeycomb-like rEGO/GP fibers. Superior electrochemical performance was achieved for solid-state supercapacitors. Abstract: Graphene-based fibers have attracted intense interests for fiber-shaped flexible supercapacitors. The pseudocapacitance materials such as transition metal oxides or conductive polymers have been widely deposited onto the surface of the graphene-based fibers to enhance their capacitive performance. Here, the flexible, bendable and knittable polyaniline (PANI)@reduced expandable graphene oxide (rEGO)/graphite powder (GP) (PANI@rEGO/GP) electrode with PANI in the well-defined porous rEGO/GP fiber was fabricated for high performance fiber-shaped solid state supercapacitors, via the in-situ electropolymerization of the aniline monomer adsorbed in the porous rEGO/GP fiber, which was prepared by the wet spinning of the expandable graphene oxide (EGO) with graphite powder as spacer, followed with reduction. Compared with the rEGO/GP@PANI electrode with PANI on the surface, the structural and electrochemical stability have been obviously enhanced for the solid state fiber-shaped symmetric supercapacitor of the proposed PANI@rEGO/GP fiber electrode, demonstrating the promising potential for practical application in the high performance fiber-shaped solid state supercapacitors. Graphical abstract: Image, graphical abstract